2023
DOI: 10.1002/jsfa.12767
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of liquid fertilizer management improves grain yield, biomass accumulation, and nutrient uptake of late‐season indica fragrant rice

Abstract: BackgroundThe use of liquid fertilizer is an effective measure to increase rice yield and nitrogen use efficiency. There has been a lack of information regarding the effects on the grain yield, biomass accumulation, and nutrient uptake in late‐season indica fragrant rice of split fertilizer application and of nitrogen management in liquid fertilizer application.ResultsA 2‐year field experiment was carried out during 2019 and 2020 with two fragrant rice cultivars grown under differing fertilizer management trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Studied has showed that fertilization application could increase dry matter accumulation in each part, promote dry matter transport from stem and leave to panicle, and signi cantly increase the contribution rate of material assimilation at the late heading stage. The study revealed fertilization application could increase rice dry matter by (Wang et al, 2023); The present study was found that the application of biochar could increase the accumulation of dry matter in the above-ground part of rice (Fig. 1,2), and reached the maximum at the maturity stage.…”
Section: Discussionsupporting
confidence: 54%
“…Studied has showed that fertilization application could increase dry matter accumulation in each part, promote dry matter transport from stem and leave to panicle, and signi cantly increase the contribution rate of material assimilation at the late heading stage. The study revealed fertilization application could increase rice dry matter by (Wang et al, 2023); The present study was found that the application of biochar could increase the accumulation of dry matter in the above-ground part of rice (Fig. 1,2), and reached the maximum at the maturity stage.…”
Section: Discussionsupporting
confidence: 54%
“…The annual import volume has reached 3 million tons [ 3 ]. The development of high-quality germplasm resources and the establishment of high-quality and high-yield cultivation technology system for fragrant rice are two important steps to promote the formation of fragrant rice quality [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%